GENDER ANALYSIS ON THE MISIOGYNIS HADITHS IN AL-KUTUB AL-TIS’AH - Najwah, Nurun (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2021)
In patriarchal culture, some hadith texts are as main sources of legitimacy for dehumanization of women. The hadith texts are documented in the popular hadith books. This, encourages the strong notion that Islam supports discrimination against women. Whereas, the Prophet Muhammad SAW. has made great efforts in humanizing women. The role of the Prophet in humanizing women is manifested in the discourse of hadith. thus, a new understanding is needed in interpreting misogynistic hadiths. In this context, this study aims to reread the misogynistic hadiths in al-Kutub al-Tis’ah (Sahih al-Bukhari, Sahih Muslim, Sunan Abu Dawud, Sunan at-Turmudzi, Sunan Ibn Majah, Sunan ad-Darimi, Musnad Muwaththa’ Iman Malik, Musnad Ahmad bin Hanbal) that related to women as personal, worship, marriage, and public spaces. To achieve this purpose, this study uses takhrij method by confirming from various hadith. As part of the data analysis, this study used gender analysis to map the form of discrimination and reinterpretation of the hadiths. The study conclude that there are 60 misogynistic hadith texts in five forms (22 subordinations, 18 violence, 15 stereotypes, 3 marginalizations, and 2 double burdens), caused by textual, partial and unhistorical interpretations. The rereading of the hadith texts is done holistically by linking and presenting verses of the Qur’an, hadiths and other texts integratively, comprehensively, taking into account historical aspects, and basic ideas of hadith. Keywords: Hadith Text, Misogynist, al-Kutub al-Tis`ah, Humanizing Women